Atrial fibrillation and stroke in adult patients with atrial septal defect and the long-term effect of closure. Issue 9 (17th February 2015) - Nyboe, C; Olsen, M S; Nielsen-Kudsk, J E; Hjortdal, V E
Abstract : Objective: To estimate the risk of atrial fibrillation (AF) and stroke and the impact of closure in patients with atrial septal defect (ASD) compared with a general population cohort. Methods: All adult Danish patients (>18 years) diagnosed with ASD from 1977 to 2009 (N=1168) were identified through population-based registries. Using Cox regression, we compared ASD patients' risk of AF and stroke with an age-matched and gender-matched comparison cohort. We computed prevalence proportions of anticoagulation and antiarrhythmic medicine use before and after closure and described stroke-related mortality. Results: Median follow-up was 9.6 years (range 1–33 years). Patients with ASD had a higher risk of first-time AF (adjusted HR 8.2; 95% CI 6.6 to 10.2) after closure than the comparison cohort, but with no difference between transcatheter and surgical closure (HR 1.5, 95% CI 0.6 to 3.5). Patients without prevalent AF had a 10-year cumulative incidence of AF of 11% (95% CI 9% to 14%) after closure compared with 2% (95% CI 1.8% to 2.5%) in the comparison cohort. Patients with ASD with prevalent AF continued to use anticoagulation medicine after closure/diagnosis. Patients with ASD had increased risk of stroke without closure (adjusted HR 2.6; 95% CI 1.4 to 3.0) and with closure (adjusted HR 2.0; 95% CI 1.4 to 2.7). Risk of stroke after closure was related to AF (HR adjusted for AF 1.3; 95% CI 0.9 to 1.9). Conclusions: Patients with ASD had a higher risk of first-time AF after closure than the comparison cohort. There was no effect of closure on the use of AF-related medicine in patients with prevalent AF.